Clinicopathologic features of primary intraosseous carcinoma in situ arising from odontogenic keratocyst: A case report and literature review - Toh, Aileen Qiu Jin; Khoo, Ui-Soon; Choi, Wing Shan; Su, Yu-Xiong (Journal of oral and maxillofacial surgery, medicine, and pathology, 2021)
The primary intraosseous carcinoma (PIOC) arising from an odontogenic keratocyst (OKC) is an exceedingly rare entity with only about 30 documented cases over the past eight decades. Although there have been documented cases in literature, few actually describe early carcinomatous change within benign cyst epithelial lining. We present a case of PIOC in situ arising from an OKC in a 54 year-old female, providing histological evidence of early transition of benign cyst epithelial lining into squamous cell carcinoma.